The occurrence of Pandalopsis spinosior Hanamura, Kohno & Sakaji, 2000 (Crustacea: Decapoda: Caridea: Pandalidae) in Hokkaido, northern Japan, and reassessment of its diagnostic characters - Hibino, Mai; Matsuzaki, Koji; Komai, Tomoyuki (Zootaxa, 2015)
Pandalopsis spinosior Hanamura, Kohno & Sakaji, 2000 (Decapoda: Caridea: Pandalidae) was originally described on the basis of material collected in the Urup Strait, South Kurile Islands, but there have been no subsequent records of the species since the original description. The Marine Science Museum, Fukushima Prefecture (Aquamarine Fukushima) has carried out investigations on deep-water animals in the Nemuro Strait, off Shiretoko Peninsula, Hokkaido, Japan, amongst the collections a large, commercially important pandalid shrimp routinely identified with P. coccinata Urita, 1941. Examination of the specimens from the collections, however, resulted in an unexpected identification with P. spinosior, instead of P. coccinata. In this short article, diagnostic characters of P. spinosior are reassessed, and comparison with P. coccinata is made. The validity of P. zarenkovi Ivanov & Sokolov, 2001, for which possible synonymy with P. spinosior was suggested, is maintained for the time being.